2016
DOI: 10.1021/jacs.5b13450
|View full text |Cite
|
Sign up to set email alerts
|

Dual C–F, C–H Functionalization via Photocatalysis: Access to Multifluorinated Biaryls

Abstract: Multifluorinated biaryls are challenging to synthesize and yet an important class of molecules. Owing to the difficulty associated with selective fluorination, this class of molecules represent a formidable synthetic challenge. An alternative approach to selective fluorination of biaryls is to couple an arene which already possess C–F bonds in the desired location. This strategy has been regularly utilized, relying heavily on traditional cross-coupling strategies which employ organometallics and halides (or ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 47 publications
1
84
0
3
Order By: Relevance
“…The overlap in the potential range of the oxidation signal of Ir III /Ir II (from −1.55 to −0.78 V) and the reduction signal of PhCl/Ph .− Cl (from −1.27 to −2.22 V) indicates that the process is thermodynamically feasible. The similar reduction of Ar−Cl to the radical anion Ar .− Cl by Ir II in the presence of diisopropylethylamine (DIPEA) was reported by Senaweera and Weaver . The Ar 2 S − anion reacts with II to give the sulfur‐centered radical anion III , and single‐electron transfer from III to Ar 2 S .…”
Section: Optimization Of the Reaction Conditions For The Visible‐lighsupporting
confidence: 64%
“…The overlap in the potential range of the oxidation signal of Ir III /Ir II (from −1.55 to −0.78 V) and the reduction signal of PhCl/Ph .− Cl (from −1.27 to −2.22 V) indicates that the process is thermodynamically feasible. The similar reduction of Ar−Cl to the radical anion Ar .− Cl by Ir II in the presence of diisopropylethylamine (DIPEA) was reported by Senaweera and Weaver . The Ar 2 S − anion reacts with II to give the sulfur‐centered radical anion III , and single‐electron transfer from III to Ar 2 S .…”
Section: Optimization Of the Reaction Conditions For The Visible‐lighsupporting
confidence: 64%
“…7, 9, 12 Although many of the spectra match experiment, two of the structures had large errors (Chart 3, red). Based on the correction described above, revised structures were tested and these match the experimental values within the error expected for our scaling factors.…”
Section: Resultsmentioning
confidence: 99%
“…Returning to the problem of multifluorinated arenes, we have previously demonstrated that the perfluoroaryl radical is a powerful intermediate for the functionalization of perfluoroarenes, which can elicit C–F alkylation, 16 arylation, 17 and alkenylation. 18 While the perfluoroaryl radical has proven competent for cross-coupling, the inherent limitation is the regioselectivity of the C–F fragmentation event.…”
Section: Introductionmentioning
confidence: 99%